Pengaruh Teknik Value Clarification Technique (VCT) Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Pancasila Kelas IV SDN 9 Martapura Sumatra Selatan - Hasna Ghoitsa Shofa; Muhammad Akmansyah; Yuli Yanti (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
The low learning outcomes of students in Pancasila Education indicate the need for an instructional technique that can enhance active participation, value understanding, and students’ ability to connect learning materials with everyday life. This study aimed to examine the effect of the Value Clarification Technique (VCT) on students’ learning outcomes in Pancasila Education among fourth-grade students at SDN 9 Martapura, South Sumatra. This study employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The research sample consisted of 44 fourth-grade students divided into two groups: an experimental class and a control class, with 22 students in each group. The experimental class was taught using the Value Clarification Technique (VCT), while the control class was taught using the Small Group Discussion technique. The research instrument was a multiple-choice learning outcomes test administered as a pretest and posttest. The data were analyzed through prerequisite tests, including normality and homogeneity tests, followed by hypothesis testing using an Independent Sample t-Test with the assistance of IBM SPSS Statistics. The results showed that the mean posttest score of the experimental class was 83.18, which was higher than that of the control class, which obtained a mean score of 61.14. The hypothesis test showed a significance value of 0.000 < 0.05, indicating that the Value Clarification Technique (VCT) had a positive and significant effect on students’ learning outcomes in Pancasila Education. These findings imply that VCT can be used as an effective alternative instructional technique to promote more active, reflective, contextual, and meaningful Pancasila Education learning in elementary schools.